Pendidikan Karakter Tokoh Bethara Guru dalam Lakon Bethara Guru Krama Wayang Topeng Tengger - Permata Raharjo, Resdianto; Ahmadi, Anas; Ikhwan, Wahid Khoirul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The formation of community character is inseparable from the prevailing environmental conditions, customs and culture. Like the figures and role models in folklore, one of them is the character Bethara Guru in the Lakon Bethara Guru Krama in the Wayang Topeng Tengger. This study aims to present the results of the analysis of character education contained in the example of the character Bethara Guru in the Lakon Bethara Guru Krama Wayang Topeng Tengger. The character traits and stories in the Lakon Bethara Guru Krama can be used as a form of material and a basis for submission to build and educate one’s individual character, both formal and non-formal. The central figure in each generation in the Lakon Bethara Guru Krama has several attitudes that should be studied and emulated. This research was compiled using a qualitative approach based on data sources and research data on the form of oral literature in the form of the story of the Lakon Bethara Guru Krama which was delivered by the puppeteer Ki Lebari at a mask puppet performance in Wonosari village, Sumber sub-district, Probolinggo district. The data collection technique in this study used note-taking and record techniques. The research model in this study uses content analysis. Test validity of the data in this study using the adequacy of referential materials. Data analysis techniques in this study included (1) transcription of recorded data, (2) transliteration of recorded data, (3) data classification, (4) structural analysis and interpretation, and (5) data testing. The result of the research is character education that can be obtained through the example of the character Bethara Guru in Bethara Guru Krama play Wayang Topeng Tengger which is a representative modification of the community with the aim of forming good character. The character of Bethara Guru in Bethara Guru Krama play is also a figure who plays an important role in modeling the formation of human character in society. Because the Bethara Guru Krama play is often performed at the Tengger Mask puppet show in traditional ruwatan ceremonies, both traditional ruwatan and children’s ruwatan.